The possibility of a tsunami warning from earthquakes Scotia Sea geophysical methods - O. I. Liashchuk (Ukrainian Antarctic Journal, 2014)
Discussed the possibility of using geophysical methods for monitoring, in particular seismic and infrasound, for an early signal of a tsunami of powerful earthquakes in the area of the Scotia Sea. Proposed to the method of early warning for station personnel.